Purification and comparative studies of dihydrolipoamide dehydrogenases from the anaerobic, glycine-utilizing bacteria Peptostreptococcus glycinophilus, Clostridium cylindrosporum, and Clostridium sporogenes. - Dietrichs, D (1990)
Three different dihydrolipoamide dehydrogenases were purified to homogenity from the anaerobic glycine-utilizing bacteria Clostridium cylindrosporum, Clostridium sporogenes, and Peptostreptococcus glycinophilus, and their basic properties were determined. The enzyme isolated from P. glycinophilus showed the properties typical of dihydrolipoamide dehydrogenases: it was a dimer with a subunit molecular mass of 53,000 and contained 1 mol of flavin adenine dinucleotide and 2 redox-active sulfhydryl groups per subunit. Only NADH was active as a coenzyme for reduction of lipoamide. Spectra of the oxidized enzyme exhibited maxima at 230, 270, 353, and 453 nm, with shoulders at 370, 425, and 485 nm. The dihydrolipoamide dehydrogenases of C. cylindrosporum and C. sporogenes were very similar in their structural properties to the enzyme of P. glycinophilus except for their coenzyme specificity. The enzyme of C. cylindrosporum used NAD(H) as well as NADP(H), whereas the enzyme of C. sporogenes reacted only with NADP(H), and no reaction could be detected with NAD(H). Antibodies raised against the dihydrolipoamide dehydrogenase of C. cylindrosporum reacted with extracts of Clostridium acidiurici, Clostridium purinolyticum, and Eubacterium angustum, whereas antibodies raised against the enzymes of P. glycinophilus and C. sporogenes showed no cross-reaction with extracts from 42 organisms tested.